Are Equity and Sustainability a Likely Outcome When Foxes and Chickens Share the Same Coop? Critiquing the Concept of Multistakeholder Governance of Food Security - McKeon, Nora (Globalizations, 2017)
This article subjects to critical analysis the rapidly expanding 'multistakeholder' approach to policy deliberation and development programming. The past 15 years have witnessed an astonishing ascension of the narrative of the corporate private sector as the new paladin of development. This dubiously accredited actor enters the development world through 'public-private partnerships' whose reputation as win-win affairs lacks validation by empirical research. The corporate sector joins-and often helps to convene-governance forums in which important policy decisions are taken and understandably deploys its efforts to further its interests. While there is a widespread aspiration today to build more inclusive, participatory governance in which the voices of those most affected by policy decisions can be heard and their rights defended, there are very great differences between this kind of practice and multistakeholder approaches in which differences in identities, interests, roles, and responsibilities are ignored and power imbalances negated. This article seeks to make the distinction clear and to identify the challenges that multistakeholderism poses for the legitimacy of governance, the protection of common goods, and the defence of human rights. It closes by pointing towards steps that could help to move from the multistakeholderism that characterizes the 2030 Agenda towards legitimate, participatory multi-actor deliberation.